The Effect of Using Laboratory Work Style on Achievement of First Year Students at Jerash University in Chemistry Laboratories and Acquisition of Practical Laboratory Skills - Qattoum, Ruba Nahar Ahmad (Dirasat: Educational Sciences, 2020)
The purpose of this study is to investigate the effect of using laboratory work on achievement of first year students at Jerash University in chemistry laboratories and the acquisition of laboratory skills. The study used a sample of (46) of first year male and female students in Chemistry laboratories in Jerash university who registered general practical chemistry lab and were divided into two groups selected by using the purposive (convenient) sampling. The first experimental group (24 students) studied laboratory work using the cooperative method and a control group (22 students) which studied using conventional method. To collect data, two methods were used: achievement test and laboratory skills measuring scale. The study found that there were statistically significant differences in students’ achievement and the acquisition of laboratory skills attributed to laboratory work in favour of the experiemtal group whreas there were no statistically significant differences attributed to gender effect on achievement and acquisition of laboratory skills nor to the interaction between laboratory work and gender in achievement and acquisition of laboratory skills. The researcher recommends the adoption of the cooperative method in chemistry laboratories for first year students at Jerash University in light of the criterion of improving university study and the acquistion of related chemical laboratory skills.